LEUKEMIA CUTIS AS A SIGN OF PROGRESSION OF MYELODYSPLASTIC SYNDROME TO ACUTE MYELOID LEUKEMIA - Marinho, Flávia Estrela Maroja; Nishimori, Fátima Satomi; Silva, Pedro Etienne Arreguy Rodrigues; Avelleira, João Carlos Regazzi; Vasconcelos, Laura Cardoso; Filgueiras, Rose Lady Dutra (Journal of the Portuguese Society of Dermatology and Venereology, 2014)
Cutaneous involvement by myeloid leukemic cells is an unusual phenomenon. The authors analyze the case of a 55-year-old male patient with myelodysplastic syndrome who presented erythematous papules on the face, trunk, arms and legs. Skin biopsy showed a dermal infiltration caused by blast myeloid cells. Immunohistochemical analysis was positive for myeloperoxidase, confirming leukemia cutis. Acute myeloid leukemia was diagnosed and the patient was treated with chemotherapy and then with rescue chemotherapy but without response. The haematologic disease progressed and the patient died after four months. The diagnosis of leukemia cutis in patients with myelodysplastic syndrome is indicative of concomitant or impending acute leukemic transformation. Early recognition is essential with important therapeutic and prognostic implications.